2019
DOI: 10.3390/ijms20174247
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine Suppresses Glutamate- and GABA-Mediated Neurotransmission by Altering SNARE Complex

Abstract: Major depressive disorder is one of the most common neuropsychiatric disorders worldwide. The treatment of choice that shows good efficacy in mood stabilization is based on selective serotonin reuptake inhibitors (SSRIs). Their primary mechanism of action is considered to be the increased synaptic concentration of serotonin through blockade of the serotonin transporter (SERT). In this study, we described an alternative mode of action of fluoxetine (FLX), which is a representative member of the SSRI class of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 59 publications
1
12
0
1
Order By: Relevance
“…Administration of fluoxetine in our study restored the levels of SE, NE, and DA, and moreover, it increased the level of Glu while the level of GABA was significantly reduced as compared to depressed group. These results agreed with those of Bymaster et al [23] and Lazarevic et al [24] who reported that in rat prefrontal cortex, acute systemic Values represent the mean% of five mice for each group (n = 10). @ p < 0.05: Statistically significant from normal control, *p < 0.05: Statistically significant from depressed group administration of fluoxetine produced a continuous elevation in NE and DA levels.…”
Section: Discussionsupporting
confidence: 91%
“…Administration of fluoxetine in our study restored the levels of SE, NE, and DA, and moreover, it increased the level of Glu while the level of GABA was significantly reduced as compared to depressed group. These results agreed with those of Bymaster et al [23] and Lazarevic et al [24] who reported that in rat prefrontal cortex, acute systemic Values represent the mean% of five mice for each group (n = 10). @ p < 0.05: Statistically significant from normal control, *p < 0.05: Statistically significant from depressed group administration of fluoxetine produced a continuous elevation in NE and DA levels.…”
Section: Discussionsupporting
confidence: 91%
“…Secondly, fluoxetine is a representative of SSRI antidepressants. Though fluoxetine could also treat glutamate toxicity in the hippocampus ( Ludka et al, 2017 ; Lazarevic et al, 2019 ), more detection of relative molecular will be better to increase the reliability of the results. Besides, we only explore the pharmacological effects of JDTLG on the glutamatergic system.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, fluoxetine decreased glutamate synaptic release. This effect can be explained by changes in the structure of the soluble N -ethylmaleimide-sensitive factor attachment protein receptor (SNARE) complex, the effector of vesicle docking, and fusion at presynaptic membranes [ 35 ]. The same mechanism seems to be involved in the action of chronically administered venlafaxine.…”
Section: Discussionmentioning
confidence: 99%